Think Globally, Act Locally: Strategi Bisnis Digital Kreatif dan Inovatif - Sigit Pramono Hadi; Seger Santoso; Isna Wati (Universitas Maritim AMNI Semarang, 2025)
In the ever-evolving digital era, the concept of